2004
DOI: 10.1016/j.neuroscience.2004.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment reduces the mnemonic and neural benefits of estrogen

Abstract: The degree to which memory is enhanced by estrogen replacement in postmenopausal women may depend on environmental factors such as education. The present study utilized an animal model of environmental enrichment to determine whether environmental factors influence the mnemonic and neural response to estrogen. Female mice were raised in standard (SC) or enriched (EC) conditions from weaning until adulthood (7 months). All mice were ovariectomized at 10 weeks, and tested in object recognition and water-escape m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 95 publications
10
80
0
1
Order By: Relevance
“…The present study replicates our previous reports demonstrating that posttraining 0.2 mg/kg 17β-estradiol enhances object memory tested 48 hours after the sample phase (Gresack & Frick, 2004, 2006, and extends this work to show that this enhancement involves the activation of NMDA receptors and PKA within the dorsal hippocampus. To our knowledge, this is the first evidence that estradiol-induced enhancement of memory consolidation involves these pathways.…”
Section: Discussionsupporting
confidence: 92%
“…The present study replicates our previous reports demonstrating that posttraining 0.2 mg/kg 17β-estradiol enhances object memory tested 48 hours after the sample phase (Gresack & Frick, 2004, 2006, and extends this work to show that this enhancement involves the activation of NMDA receptors and PKA within the dorsal hippocampus. To our knowledge, this is the first evidence that estradiol-induced enhancement of memory consolidation involves these pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps our handling procedure may have negated estrogen's effects on the Y-maze because of the enriched setting. Environmental enrichment can increase spatial memory ability on several tasks (Fernandez-Teruel et al, 1997;Gresack and Frick, 2004). However, a recent finding demonstrated that while mice treated with estrogen had improved spatial memory, estrogen combined with previous exposure to an enriched environment did not alter object recognition and actually impaired work memory acquisition (Gresack and Frick, 2004).…”
Section: The Lack Of An Estrogen Influence On Hippocampal Morphology mentioning
confidence: 99%
“…Estrogen is thought to be beneficial for memory because it enhances the structure and function of mnemonic brain regions such as the hippocampus that deteriorate in normal aging and Alzheimer's disease (Foy, Xu, Xie, Brinton, Thompson & Berger, 1999;Warren, Humphreys, Juraska & Greenough, 1995;Woolley & McEwen, 1992, and because hippocampal-dependent memory (e.g., spatial memory, object recognition) is typically improved by exogenous estrogen administration in young ovariectomized female rats (Bimonte & Denenberg, 1999;Daniel, Fader, Spencer & Dohanich, 1997;Gibbs, 1999;O'Neal, Means, Poole & Hamm, 1996;Sandstrom & Williams, 2001) and mice (Gresack & Frick, 2004, 2006bHeikkinen, Puoliväli, Liu, Rissanen & Tanila, 2002;Rissanen, Puoliväli, van Groen & Riekkinen, 1999). Estrogen is also a trophic factor for the adult hippocampus (Brinton, 2001), and therefore, estrogen deficiency during aging may render the hippocampus more vulnerable to deterioration and exacerbate emerging age-related memory deficits.…”
Section: Introductionmentioning
confidence: 99%